2021
DOI: 10.1155/2021/1757401
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Postpartum Intrauterine Contraceptive Device Uptake among Women Delivering in Public Hospitals of South Gondar Zone, Northwest Ethiopia, 2019: An Unmatched Case-Control Study

Abstract: Introduction. Integrated use of postpartum intrauterine contraceptive devices with delivery service during the immediate postpartum period is ideal for both women and health-care providers. However, utilization of intrauterine contraceptive devices during the postpartum period was rare and in Ethiopia, with information regarding uptake of postpartum intrauterine contraceptive devices limited. Objective. Identify determinants of postpartum intrauterine contraceptive devices uptake among women delivering in publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 11 publications
4
19
0
Order By: Relevance
“…Mothers having greater than 3 children were 4.5 times more likely to utilize immediate PPIUCD than their counterparts. This association was consistent with a studie conducted in China (35), Nigeria(39), Ruwanda-(4, 21) and other part of Ethiopia (34,40,41). The possible justi cation might be that mothers who have a large number of children may be inspired to prevent additional pregnancy to limit their family size.…”
Section: Discussionsupporting
confidence: 88%
“…Mothers having greater than 3 children were 4.5 times more likely to utilize immediate PPIUCD than their counterparts. This association was consistent with a studie conducted in China (35), Nigeria(39), Ruwanda-(4, 21) and other part of Ethiopia (34,40,41). The possible justi cation might be that mothers who have a large number of children may be inspired to prevent additional pregnancy to limit their family size.…”
Section: Discussionsupporting
confidence: 88%
“…In the present review and meta-analysis, subgroup analysis was done by regions, study population, and study design indicated that there were variations in the utilisation of PPIUCD among different included regions, population and study design in Ethiopia. Accordingly, the highest in utilization of PPIUCD was observed in Addis Ababa 25.68% (95% CI: 11.07, 40.29) [ 27 , 32 34 ], 34.09% (95% CI: 32.52, 35.66) [ 32 , 35 ], and 21.63% (95% CI: 14.45, 28.81) [ 26 , 32 , 36 ] by region, study population and study design respectively. The observed differences could be due to culture, residence, educational status and religious differences across the region.…”
Section: Discussionmentioning
confidence: 99%
“…Counselling of couples, focusing on male involvement have also been suggested, although all men do not willingly accompany women to antenatal clinic [ 45 47 ]. Studies in LMICs show that a substantial proportion of women did not use modern contraceptive methods in the first year after birth and maternal services were found to be the sole predictors in postpartum contraceptive use.…”
Section: Discussionmentioning
confidence: 99%
“…Counselling of couples, focusing on male involvement have also been suggested, although all men do not willingly accompany women to antenatal clinic [45][46][47].…”
Section: Discussionmentioning
confidence: 99%